Comparative analysis of packet fragmentation on the MPLS unicast IP routing: article / Suraya Zainuddin - Zainuddin, Suraya (2015)
Multiprotocol Label Switching (MPLS) is a standard architecture proposed by the Internet Engineering Task Force (IETF) that integrates label swapping forwarding with network layer routing. It is a promising effort in order to deliver better network performance. MPLS is acknowledged and widely been used to overcome drawbacks introduce by traditional IP routing. This paper discussed on the network performance with the effect of packet fragmentation over IP and MPLS networks. In real implementation, fragmented IPv4 traffic causes a lot of problem such as increase load at router CPUs and also result in poor performance or even total communication failure. In addition, traffic fragmentation is used in numerous network attacks. Thus, we want to avoid the fragmentation at all or ensure the network is insulated from fragmented traffic. However, in some cases when using IPv4 fragmentation is unavoidable. Simulation models were developed using Graphical Network Simulator GNS3 to compare performance of Open Shortest Path First (OSPF) and MPLS network. Performance is determined by Round-Trip-Time (RTT), calculated throughput and packet loss. Analysis shows different protocols, data sizes and MTUs influence network performance. OSPF provides better RTT and throughput compared to MPLS with default MTU setting. However, better RTT and calculated throughput performance can be achieved by increasing the MTU for interface, IP and MPLS. Finally, the study also indicates packet fragmentation could degrades network performance in both network topologies.